Pandemic and Social Capital: Synthesis Model for "Jogo Tonggo" Policy Implementation - Wahyu Prasetyo, Andri; Mutiara Fauziah, Nike; Puja Kesuma, Agung (KnE Social Sciences, 2023)
One of the regions that received the Regional Innovation award in a Productive and Safe New Normal Order for COVID-19 was Central Java Province through the policy of the Jogo Tonggo Task Force. Based on several previous research results related to policy evaluation, it is seen that this policy is still ineffective in suppressing the spread of COVID-19 because each region has different social capital and complexity of implementing policies. This article aims to formulate a conceptual framework for policy implementation based on the Synthesis Model for the Jogo Tonggo policy. This article uses a qualitative approach with a literature study method. The result of this research is the conceptual framework for implementing the Jogo Tonggo policy with the Hybrid Model approach. That approach analyzes what is obtained and what is done by the policy implementer and the interaction between human resources, policy factors, and the place where the policy is implemented. This research is important as a reference for formulating social capital-based policies in reducing and as an effort to mitigate disaster risk at the local government level, especially in Central Java. Keywords: Pandemic, Social Capital, “Jogo Tonggo” Policy, Hybrid Model, Policy Implementation